PERICRANIAL MEMBRANE-INDUCED OSSIFICATION IN CRANIOPLASTY AUTOGRAFT: EVIDENCE OF RANKL-MEDIATED BONE REMODELING - Apriawan, Tedy; Armando, Alivery Raihanada; Fauzi, Asra Al (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Bone resorption is a major complication after cranioplasty, often due to impaired osteogenesis and vascularization. The pericranial membrane has osteogenic properties and can enhance bone regeneration by modulating signaling pathways involved in bone remodeling. RANKL is a key regulator of osteoblast and osteoclast activity during bone healing. This study aimed to analyzed the mechanism of RANKL present in the pericranial membrane to Induced Accelerated Ossification in the cranioplasty procedure. The methods was an experimental study using 35 male Oryctolagus cuniculus rabbits divided into three groups, a negative control (bone defect without graft), a positive control (autograft without pericranial membrane), and a treatment group (autograft with pericranial membrane). RANKL expression was evaluated at weeks 6 and 12 using immunohistochemistry. Data were analyzed using ANOVA and Mann-Whitney test with a significance level of p<0,05. The result are RANKL expression in weeks 6, the treatment group shows the highest RANKL expression (5,2) compared to the positive control (4,7) and negative control (4,3). At week 12, RANKL expression decreases in all groups, with the lowest value in the treatment group (0,9). Comparison of weeks 6 and 12 showed a significant difference in all groups (p<0,05). Conclusion: The pericranial membrane plays a role in accelerating the ossification process of cranioplasty autografts by modulating RANKL expression. Increased RANKL in the early phase and decreased in the late phase indicate faster bone formation and remodeling in the treatment group. These findings support the use of the success of cranioplasty and reduce the risk of bone resorption.